# AKAR PANGKAT

1.

2 −2 =

1
23
2
a4

2.

2a − 4 =

3.

5−3 x5−4 = 5−7

3

4.

 3−1 
3−3 7 6
 − 2  = − 6 . 3
7 3
7 

5.

1
p
=
−1
5p
5

6.

( 2 x ) 2 : ( x −1 ) −3
y7

2y

=

2 2 x 2 x −6 2 2 x 2 2 y
:
= 7 x −6
y7 2 y
y
x

=

23 x 2 y 23 x 2 − ( −6 ) y
=
y 7 x−6
y7

23 x 8 y
= 1 6
yy
7.

3 x 3 y 5 .10 xy 4 30 x 4 y 9
=
= 6x2 y3
5x2 y 6
5x2 y 6

8.

2 x 3 y 6 .15 x8 y 2
8 x3 y 6
=
4 x 5 y 3 .3 x 2 y 3 12 x 7 y 6
120 x11 y 9 .15 x8 y 2
= 10 x 4 y 2
7 4
12 x y

6 = 2 6 2 32 = 16. 24 = 4. 10 ( − 2a ) −5 = −1 −1 a +b a − 2b − 2 1 1 =− 5 32 a 5 ( − 2a ) 1 1 b+a + b + a a 2 − b2 a b ab = = 2 2 = x 2 2 b . c 8 9 ) 2 3 − 2 = (16.2 = 4 2 3 3 2 + 8 2 − 12 2 = (3 + 8 − 12) 2 = −1 2 4 (4 5.9.3) − 4 = 48 − 4 = 44 6 = 6 5 13 13 3 2 39 2 13 2 = × = = 18 6 3 2 3 2 3 2 4 3 4 3 2 3 + 3 24 − 12 3 24 − 12 3 = × = = 12 − 9 3 2 3 −3 2 3 −3 2 3 +3 4 3 2 3 5 + 7 2 5 + 21 2 5 + 21 = × = = 5−7 −2 5− 7 5− 7 5+ 7 .a ab b 2 − a 2 − a 2 b2 a 2b 2 MERASIONALKAN 1. 2 72 − 6 200 + 3 18 = 12 2 − 60 2 + 9 2 = 39 2 6 7.

2 n 2 − 20 + 100 = 0 ( n − 10 )( n − 10 ) = 0 n − 10 = 0 n = 10 n − 10 = 0 n = 10 3. 3x 2 + 5 x − 2 = 0 ( 3x − 1)( x + 2) 3x − 1 = 0 x + 2 = 0 x1 = 1 3 x2 = 2 7 2 . 4 x 2 + 3 x − 7 = 0 ( 4 x + 7) = 0 1 4 ( 4 x − 4) x −1 = 0 4x + 7 = 0 x =1 7 x= 4 4.MEMFAKTORKAN 1 x 2 − 18 + 32 = 0 ( x − 16 )( x − 2) = 0 x − 16 = 0 x−2 =0 x=2 x1 = 16 . 7 x 2 − 37 + 10 1 ( 7 − 35 )( 7 − 2 ) 7 5 x − 7+ = 0 x2 = 7 x1 = 5 5.

x 2 − 19 x + 48 = 0 ( x − 3)( x − 16 ) x −3= 0 x − 16 = 0 x = 16 x=3 10. x 2 − 18 x + 32 = 0 ( x − 16 )( x − 2) x − 16 = 0 x − 2 = 0 x1 = 16 x2 = 2 MELENGKAPKAN KUADRAT SEMPURNA 1.6. x=2 6 x 2 + 11x − 35 = 0 ( 3 x − 5)( 2 x + 7 ) 3x − 5 = 0 2 x + 7 = 0 x1 = 5 3 x2 = −7 2 9. x 2 + 16 x + 15 = 0 x 22 + 16 x = −215 x + 16 x + 8 = −15 + 8 2 ( x + 8) 2 = −15 + 64 x + 8 = 49 x +8 = 7 x2 + 8 = −7 x1 + 8 = 7 x1 = −1 x2 = −7 − 8 x2 = −15 . 3 x 2 − 6 x = 0 3 x( x − 2 ) = 0 3x = 0 x − 2 = 0 x=0 x=2 7. 4 x 2 − 16 = 0 ( 2 x + 4)( 2 x − 4) 2x + 4 = 0 2x − 4 = 0 4 x=− 2 2x = 4 x = −2 8.

x − 3 x − 18 = 0 x 2 − 3x = 18 2 3 3 x − 3 x +   = 18 +   2 2 2 3 81  x−  = 2 4  2 2 3 9 =± 2 2 3 9 x− = 2 2 9 3 x1 = + 2 2 12 x1 = =6 2 x− 3 9 =− 2 2 9 3 x2 = − + 2 2 6 x2 = = 3 2 x2 = x − . x 2 + 2 x + 3 = 0 x2 + 2x = 3 x 2 + 2 x + 12 = 3 + 12 ( 2 x + 1) 2 = 4 x + 1 = ±2 x1 + 1 = 2 x1 = 1 x2 + 1 = −2 x2 = −1 2 3.2.